SOCIAL EMOTIONAL COMPETENCE AND PROFESSIONAL ETHICS: PROFESSIONAL CHALLENGES OF THE POLICE OFFICER IN A MULTICULTURAL SOCIETY - Treļs, Ēriks; Mihailovs, Ivans Jānis; Matisāns, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
In every profession, where basic activities are carried out in direct interaction with people, often solving diverse problem situations and providing assistance to victims, cooperating with representatives of different cultures, not only professional knowledge and skills are important, but also interpersonal cooperation and emotional skills. The aforementioned raises the issue of socio-emotional competence, which directly interacts with the professional ethics of a police officer, so that it is possible to effectively perform official duties and overcome personal and professional challenges, including in the context of a multicultural society. The purpose of the article is to describe important aspects of the interaction between the socio-emotional competence and professional ethics of a police officer, providing proposals for their promotion in professional everyday life, which would allow the police officer to overcome personal and professional challenges while performing official duties in a multicultural society. The research uses the analysis of documents and scientific literature, methods of interpretation of legal norms (historical method; teleological method; grammatical method; systemic method), analyzing regulatory acts, as well as induction and deduction methods, drawing conclusions and making proposals for the improvement of regulatory acts and police service practice.